PENGAMANAN FILE MENGGUNAKAN KRIPTOGRAFI DENGAN METODE AES-128 BERBASIS WEB DI KOMITE NASIONAL KESELAMATAN TRANSPORTASI - Dian Widyawan; Imelda Imelda (Fakultas Teknologi Informasi, Universitas Budi Luhur, 2021)
The rapid development of information and telecommunications technologies that enable people to carry out activities in the form of files or data that is confidential, hence the importance of data protection for securing confidential files. The data is the record of a collection of facts or a variable that is shaped in the form of words, images and numbers. However, sometimes the data that is private is often leaks and data loss. The use of computers became a necessity that can not be separated again for each activity, not an exception in the National Transportation Safety Committee work in the field of investigation. For the sake of fluency in the investigation to that required an application to maintain the confidentiality of the data. This study aims to produce applications to assist in the process of securing data. Cryptographic techniques used are methods Advanced Encryption Standard (AES) is designed with one of the main applications of sorts - kind of method, the method of Waterfall, at the design stage of security applications using the programming language PHP files using web based MySQL database. MethodAdvanced Encryption Standard(AES) is an encryption standard by the symmetric key with key sizes vary as 128 bits, 192 bits, and 256 bits. From the results of the implementation can be concluded that the application was able to secure an investigation file from the original form of plaintext into ciphertext with the end result that the file can not be understood more meaning.